Rising trends and indication of Caesarean section in Indonesia - Ali Sungkar; Ray Wagiu Basrowi (Indonesian Nutrition Association, 2020)
The rate of Caesarean delivery is rising dramatically worldwide, and also nationally. The number of Caesarean births exceeds the WHO recommended rate. This study aims to provide an overview of current increasing trend of Caesarean section, including elective procedure, and its risk. A review was conducted using online database, surveillance reports, and national surveys to identify studies with topics of prevalence, trend, indications, and risks of Caesarean delivery. Overall, there is an increase of Caesarean section in global, Asia, and Indonesia setting. We found an increase of 8% from 2013 to 2018 based on population survey, and increase of elective Caesarean surgery, particularly in tertiary care. We listed the possible health risks in short term, long term among mothers and child. Advanced maternal age, higher socio-economic status, higher educational level, residing in urban area, and ownership of health insurance were found to be factors associated with maternal choice on Caesarean delivery. The information presented is important to raise awareness among policy makers aimed to develop a national strategy in reducing the rate of Caesarean delivery.